One fine day - Hogrorian, Nonny (New York : Aladdin Paperbacks, 1971)
"One fine day a fox travelled through the great forest. When he reached the other side he was very thirsty. The jaunty red fox stole milk from an old farm woman, lost his tail under the annoyed woman's knife and spent the day bargaining to get it back.
TR/PS
Keywords: Foxes -- Fiction; Children stories; Humor -- Fiction